Differential responses of major vegetable aphids to newer insecticide molecules - Halder, Jaydeep; Kodandaram, MH; Rai, AB (Vegetable Science, 2011)
Insects are one of the major limiting biotic factors for production of vegetables in India. Among these, the aphids alone have the potential to inflict monetary loss in the tune of Rs. 2000-2600 per hectare at 8-10% infestation (Mistric and Clark., 1979). Besides sucking the sap and there by devitalizing the plants many of them serve as a vector in transmitting the viral diseases. Most of the vegetable crops including cabbage, cauliflower, radish, cowpea, chilies, brinjal and field bean are highly infested with different aphid species through out their growing period. At present there is a great deal of discussion on the resistance and resurgence of insects to commonly used insecticides which is of a grave concern in crop protection. One of the solutions to the resistance problem is the rotation of newer insecticides with the conventional ones. Hence, an attempt has been made to evaluate newer insecticidal molecules to manage different vegetable aphids viz. Myzus persicae, Brevicoryne brassicae and Aphis gossypii. Accordingly, toxicity of three newer molecules viz., imidacloprid, thiamethoxam and diafenthiuron were compared with most commonly used conventional insecticides like dimethoate and acephate in vegetable ecosystem.